El liderazgo político en la presidencia de Felipe Calderón (2006-2012). - Luis Méndez, José (El Colegio de México A.C., 2015)
Presidents face the problem of exercising a leadership that is of an elusive nature, hard to comprehend and to grasp, and that involves both opportunities and risks. Political leaders may confront such questions more effectively  and academics and citizens alike may better evaluate them if they understand leadership as “strategic action.” In support of this hypothesis, this paper sets out three elements: “relevant agenda”, “inclusive leveraging” and “balanced decisión making style”. On this basis an analysis is made of the government of Felipe Calderón, concluding that he failed to exercise political leadership.